2016
DOI: 10.1103/physrevb.93.020507
|View full text |Cite
|
Sign up to set email alerts
|

Interface-enhanced electron-phonon coupling and high-temperature superconductivity in potassium-coated ultrathin FeSe films onSrTiO3

Abstract: Alkali-metal (potassium) adsorption on FeSe thin films with thickness from two unit cells (UC) to 4-UC on SrTiO 3 grown by molecular beam epitaxy is investigated with a low-temperature scanning tunneling microscope. At appropriate potassium coverage (0.2−0.3 monolayer), the tunneling spectra of the films all exhibit a superconducting-like gap larger than 11 meV (five times the gap value of bulk FeSe), and two distinct features of characteristic phonon modes at ~11 meV and ~21 meV. The results reveal the critic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
53
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 56 publications
14
53
2
1
Order By: Relevance
“…The molecule/FeSe system was modeled using a slab model containing an isolated molecule adsorbed on a In contrast, the acceptor-type TCNQ molecules tend to extract electrons from the substrate, and are preferentially adsorbed on the SC area where the electron concentration is higher. Similar selective adsorption behaviors induced by charge density inhomogeneity have been reported -an acceptor molecule, F 16 CuPc, preferred to adsorb on more negatively charged monolayer graphene than bilayer graphene on SiC substrate [33,34].…”
Section: Experimental and Theoretical Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…The molecule/FeSe system was modeled using a slab model containing an isolated molecule adsorbed on a In contrast, the acceptor-type TCNQ molecules tend to extract electrons from the substrate, and are preferentially adsorbed on the SC area where the electron concentration is higher. Similar selective adsorption behaviors induced by charge density inhomogeneity have been reported -an acceptor molecule, F 16 CuPc, preferred to adsorb on more negatively charged monolayer graphene than bilayer graphene on SiC substrate [33,34].…”
Section: Experimental and Theoretical Methodssupporting
confidence: 61%
“…Different from K atoms, which tend to adsorb individually at low coverage and spread all over the substrate [16][17][18], DBTTF (TCNQ) molecules coalesce into islands (clusters) and leave bare FeSe areas, which enable us to study a localized superconducting transition with spatial resolution. The superconductivity on the 1st…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They estimated the electron-phonon coupling constant, λ, to be 0.5 from the relative intensity of replica bands. Large electron-phonon coupling to STO substrates was also suggested by some other experimental results [151,159,160]. However, at present, there are no experimental results that demonstrate the direct relation between the electron-phonon coupling and the enhancement of the superconductivity.…”
Section: -System MLmentioning
confidence: 82%
“…They also found that the superconducting phase of 3-ML thick films is dome-shaped in a temperature-vs-doping-level phase diagram, suggesting an unconventional mechanism for the superconductivity. Subsequently, the K-adsorption effects were investigated in detail by other several research groups using ARPES [148,149] or STM/STS [150][151][152], and their common results were that the electron-doping can enhance the superconductivity even for a 50-ML-thick FeSe film [149] and the superconducting gap size of the doped samples becomes larger as the thickness becomes thinner, suggesting an interfacial effect for the enhancement of superconductivity in monolayer FeSe.…”
Section: -System MLmentioning
confidence: 99%